ORBITAL REMOTE SENSING FOR EVAPOTRANSPIRATION MODELING: THEORETICAL OVERVIEW AND APPLICATIONS IN CLOUD COMPUTING - Silva, César de Oliveira Ferreira; Magnoni, Pedro Henrique Jandreice [UNESP]; Manzione, Rodrigo Lilla [UNESP] (Universidade Estadual Paulista - Campus de Tupa, 2021)
The objective of this review article was to compile the theoretical and technological aspects of remote sensing-based evapotranspiration (ET) modeling. We surveyed the thermohydrological concepts that support the ET phenomenon, such as soil energy fluxes (thermo) and hydrological balance. We also present the main variants of the ET concept. We survey the most disseminated models applied to satellite imagery (to be implemented by the researcher) and present their assumptions, limitations, and opportunities. Models based on remote sensing focus on the actual ET. Finally, we surveyed ready-made actual ET databases (available on Google Earth Engine - GEE), and for these, we developed interactive panels, for data extraction. With these panels, it is possible to easily extract actual ET time series and perform subsequent calibrations with field data.
TELEDETECCIÓN ORBITAL PARA MODELAMIENTO DE LA EVAPOTRANSPIRACIÓN: PANORAMA TEÓRICO Y APLICACIONES EN LA COMPUTACIÓN EN NUBE
SENSORIAMENTO REMOTO ORBITAL PARA MODELAGEM DA EVAPOTRANSPIRAÇÃO: SÍNTESE TEÓRICA E APLICAÇÕES EM COMPUTAÇÃO NA NUVEM
Keywords: Agrometeorology; Automation; Google Earth Engine; Hydrology; Modeling